PHYTOTOXIC CONSTITUENTS FROM ENDOPHYTIC FUNGUS Xylaria cubensis ASSOCIATED WITH Eugenia brasiliensis - Biasetto, Carolina R. [UNESP] (2019)
The upscaling of Xylaria cubensis, an endophyte of Eugenia brasiliensis (Myrtaceae), in PDB medium led to the isolation of known compounds including cytochalasin D (7) and cytochalasin C (8), which exhibited relatively higher phytotoxic activity in all the concentrations tested compared to the commercial herbicide GOAL (R). Besides the aforementioned metabolites, one dikctopiperazinc (DKP) and two isocoumarins were isolated and two DKPs were also identified in the mixture. The structures were determined by 1D and 2D H-1 NMR, MS analyses and were compared with the literature.